Electrolyte-gated n-type transistors produced from aqueous inks of WS2 nanosheets - Higgins, Thomas M.; Matthiesen, Maik; Grieger, Sebastian; Synnatschke, Kevin; Brohmann, Maximilian; Rother, Marcel; Backes, Claudia; Zaumseil, Jana (Advanced functional materials, 2019)
Solution-processed, low cost thin films of layered semiconductors such as transition metal dichalcogenides (TMDs) are potential candidates for future printed electronics. Here, n-type electrolyte-gated transistors (EGTs) based on porous WS2 nanosheet networks as the semiconductor are demonstrated. The WS2 nanosheets are liquid phase exfoliated to form aqueous/surfactant stabilized inks, and deposited at low temperatures (T < 120 °C) in ambient atmosphere by airbrushing. No solvent exchange, further additives, or complicated processing steps are required. While the EGTs are primarily n-type (electron accumulation), some hole transport is also observable. The EGTs show current modulations > 104 with low hysteresis, channel width-normalized on-conductances of up to 0.27 µS µm−1 and estimated electron mobilities around 0.01 cm2 V−1 s−1. In addition, the WS2 nanosheet networks exhibit relatively high volumetric capacitance values of 30 F cm−3. Charge transport within the network depends significantly on the applied lateral electric field and is thermally activated, which supports the notion that hopping between nanosheets is a major limiting factor for these networks and their future application.